The prevalence and outcomes of hyponatremia in children with COVID-19 and multisystem inflammatory syndrome in children (MIS-C) - Dalal, Neal; Pfaff, Mairead; Silver, Layne; Glater-Welt, Lily; Sethna, Christine; Singer, Pamela; Castellanos-Reyes, Laura; Basalely, Abby (Frontiers in Pediatrics, 2023)
Abstract: Introduction To assess the prevalence of hyponatremia among pediatric patients with coronavirus disease 2019 (COVID-19) and Multisystem Inflammatory Syndrome in Children (MIS-C) and determine if pediatric hyponatremia was associated with an increased length of stay, higher rates of mechanical ventilation, and/or elevated inflammatory markers on admission as compared to eunatremic patients. Methods Electronic health records were retrospectively analyzed for 168 children less than 18 years old with COVID-19 or MIS-C who were admitted to pediatric units within the Northwell Health system. The primary exposure was hyponatremic status (serum sodium <135 mEq/L) and the primary outcomes were length of stay, mechanical ventilation usage and increased inflammatory markers. Results Of the 168 children in the study cohort, 95 (56%) were admitted for COVID-19 and 73 (43.5%) for MIS-C. Overall, 60 (35.7%) patients presented with hyponatremia on admission. Patients with hyponatremia had higher rates of intensive care unit admission when compared to eunatremic patients (32/60 [53.3%] vs 39/108 [36.1%], p = 0.030). In regression models, hyponatremia was not significantly associated with increased length of stay or mechanical ventilation rates. After adjustment for relevant confounders, hyponatremia remained associated with an increased square root CRP (β = 1.79: 95% CI 0.22-3.36) and lower albumin levels (β = -0.22: 95% CI -0.42- -0.01). Conclusion Hyponatremia is common in pediatric COVID-19 and MIS-C. Hyponatremia was associated with a lower albumin and higher square root CRP levels. This may suggest an association of inflammation with lower serum sodium levels.